CGIAR Research Program on Maize - Plan of Work and Budget 2021 - CGIAR Research Program on Maize (CGIAR Research Program on Maize, 2021)
Led by the International Maize and Wheat Improvement Center (CIMMYT), with the International Institute of Tropical Agriculture (IITA) as its main CGIAR Consortium partner, The CGIAR Agri-food Research Program MAIZE focuses on increasing maize production for the 900 million poor consumers for whom maize is a staple food in Africa, South Asia and Latin America. MAIZE’s specific goal is to increase incomes and food security for poor maize producers and consumers while enhancing the sustainability of maize-based production systems and the natural resource base. MAIZE will ensure that technological and institutional innovations are developed, tested and deployed to enable profitable and equitable integration of small-scale maize producers and processors in the expanding maize value chains.